2003
DOI: 10.3168/jds.s0022-0302(03)73950-2
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Udder and Leg Hygiene Scores and Subclinical Mastitis

Abstract: The objective of this study was to determine the relationship between udder and leg hygiene scores of lactating dairy cattle and measures of subclinical mastitis. Study animals (n = 1250) consisted of lactating dairy cows from eight commercial dairy farms. Herds were enrolled during December 2000 and January 2001 and were visited bimonthly for a total of five visits per herd. Udder and leg hygiene scores were recorded by one person using a four-point scale ranging from one (very clean) to four (very dirty). Ud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

21
247
9
11

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 271 publications
(288 citation statements)
references
References 13 publications
(23 reference statements)
21
247
9
11
Order By: Relevance
“…Although that study found no health or welfare concerns for beef animals at the high stocking density, the potential for dairy cow welfare to be compromised is greater at high stocking densities, as compromised udder health is one of the main health problems of dairy cows (Grohn et al, 2005). Indeed, intramammary environmental pathogens are significantly associated with udder hygiene scores (Schreiner and Ruegg, 2003). Hence it is not surprising that the high dirtiness scores of animals confined at the high stocking density in the covered OWP in the case study was reflected in a higher tendency for mastitis-causing agents to be isolated, and higher lactation SCC in these animals.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…Although that study found no health or welfare concerns for beef animals at the high stocking density, the potential for dairy cow welfare to be compromised is greater at high stocking densities, as compromised udder health is one of the main health problems of dairy cows (Grohn et al, 2005). Indeed, intramammary environmental pathogens are significantly associated with udder hygiene scores (Schreiner and Ruegg, 2003). Hence it is not surprising that the high dirtiness scores of animals confined at the high stocking density in the covered OWP in the case study was reflected in a higher tendency for mastitis-causing agents to be isolated, and higher lactation SCC in these animals.…”
Section: Discussionmentioning
confidence: 86%
“…Winter accommodation for dairy cows also has a significant effect on SCC, animals in loose housing systems having higher scores than tied cows (Bartlett et al, 1992b). Schreiner and Ruegg (2003) found that linear SCC was also associated with leg hygiene score, and increased as udder hygiene score increased.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…An increased risk of high somatic cell count and intramammary infections has been associated with cows having dirty udders and legs (Schreiner and Ruegg, 2003;Ellis et al, 2007;Breen et al, 2009). …”
Section: Introductionmentioning
confidence: 99%
“…The incidence of mastitis in a herd is influenced by managerial and environmental factors, such as housing system, cleanliness of cows, feeding regime, hygienic quality of feed and water, milking equipment and general practices related to, for instance, drying-off (Elbers et al, 1998;Barkema et al, 1999;Peeler et al, 2000;Schreiner and Ruegg, 2003;Nyman et al, 2007). The incidence of mastitis and the impact of the disease can be reduced by mastitis control, that is, various preventive measures.…”
Section: Introductionmentioning
confidence: 99%